ZPORR nową szansą pozyskiwania dotacji inwestycyjnych przez Mikroprzedsiębiorstwa regionu Warmii i Mazur - Olkowska, Wiesława (The Integrated Regional Operational Programme (ITOP) as a New Opportunity for Obtaining Subsidies by Microbusinesses in the Region of Warmia and Mazury, 2007)
This study is an attempt at determining the level of utilizing the funds from IROP 2004-2006; Priority 3 Regional Development; Action 3.4 Microbusinesses in Warmia and Mazury. Source material from the Olsztyn RFI/IROP for the years 2004-2005 has been analyzed. The value of subsidies was established as of 31.01.2006, based on the contracts with beneficiaries as 81.01% of IROP allocation for the years 2004-2006. The level of payments from the programme accounts amounted only to 5.26% of the implementation of IROP actions for the years 2004-2006. The study has been supplemented with the results of a pilot survey concerning the significance of EU subsidies as development opportunities for microbusinesses in Warmia and Mazury.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 392-400